Pedagogical support as a means of effective training of students - Pavlova, O.; Pavlov, Y. (Problems of Engineer-Pedagogical Education, 2021)
The article analyzes modern psychological and pedagogical research, which allowed drawing conclusions about the explanation of the essence of pedagogical support and the peculiarities of its use as a means of effective training of students in a higher education institution. The essence of key concepts, such as "support", "pedagogical support", "support of professional training", is also revealed from the pedagogical and psychological point of view. The relevance and role of pedagogical support in modern higher education as a tool for identifying and understanding the new "zone of development" of the individual is substantiated. The main directions and stages of pedagogical support of students during their studies in higher education institutions and its characteristic features as an educational phenomenon are determined and characterized. The purpose of pedagogical support is determined, which is to create an orderly system of professional activity of the teacher, which would guarantee the effectiveness of vocational training and personal development of the student. Pedagogical support is considered in the article as a means of effective training of students, in connection with which the essence of the concept "means" is revealed. Emphasis is placed on the fact that pedagogical support of students in the process of vocational training is aimed at ensuring the realization of existing personal potential of students, revealing their individuality, communication skills, accumulation of professionally relevant experience, mastering the necessary methods of self-organization and self-development. A well-established mechanism of the teacher-student interaction, which includes prevention of possible difficulties or problems of the student, diagnosis of existing problems, search for their solution, counseling at the stage of their solution, helps students to best master the reflective process of professional development. It is also noted that during the implementation of pedagogical support as a means of improving the quality of vocational training of students, it is important to consider the pedagogical component, which will make the process of improving the quality of students’ vocational training purposeful and productive